2017
DOI: 10.1101/111914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic epidemiology of globalKlebsiella pneumoniaecarbapenemase (KPC)-producingEscherichia coli

Abstract: The dissemination of carbapenem resistance in Escherichia coli has major implications for the management of common human infections. bla KPC , encoding a transmissible carbapenemase (KPC), has historically largely been associated with Klebsiella pneumoniae, a predominant plasmid (pKpQIL), and a specific transposable element (Tn4401, ~10kb). Here we characterize the genetic features of the emergence of bla KPC in global E. coli, 2008-2013, using both long-and short-read whole genome sequencing.Amongst 43/45 suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Overall, among 14 K. pneumoniae strains evaluated, 4/6 (83%) ybt+ isolates (4/4 303 ST11, 1/2 ST340) killed all wax moth larvae within 96 h, compared to only 1/8 (13%) ybt-304 strains (1/1 ST258, 0/4 ST340, 0/3 ST437) (P = 0.03, Fisher's exact test), suggesting that in 305 the absence of pLVPK-like plasmids, the presence of ybt could be enough to confer enhanced 306 virulence. However, the single ST258 strain (ybt-and clb-negative), isolated from a human 307 clinical sample also killed 100% of G. mellonella within 96 h ( Figure 4C), suggesting that 308 other factors, not elucidated in this study, may also be contributing to the virulence phenotype We have identified regional bla KPC spread consistent with high prevalence of IncN 337 plasmids, previously associated with the global spread of these genes (Stoesser et al, 2017). 338…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Overall, among 14 K. pneumoniae strains evaluated, 4/6 (83%) ybt+ isolates (4/4 303 ST11, 1/2 ST340) killed all wax moth larvae within 96 h, compared to only 1/8 (13%) ybt-304 strains (1/1 ST258, 0/4 ST340, 0/3 ST437) (P = 0.03, Fisher's exact test), suggesting that in 305 the absence of pLVPK-like plasmids, the presence of ybt could be enough to confer enhanced 306 virulence. However, the single ST258 strain (ybt-and clb-negative), isolated from a human 307 clinical sample also killed 100% of G. mellonella within 96 h ( Figure 4C), suggesting that 308 other factors, not elucidated in this study, may also be contributing to the virulence phenotype We have identified regional bla KPC spread consistent with high prevalence of IncN 337 plasmids, previously associated with the global spread of these genes (Stoesser et al, 2017). 338…”
supporting
confidence: 55%
“…On the other hand, the wide diversity of Inc-type plasmids, found in this study, including 339 small mobilizable Col-like replicons could be associated with the acquisition of multiple 340 resistance mechanisms, contributing to the wider resistome. Therefore, the presence of K. 341 pneumoniae in a wide range of environmental reservoirs and hosts, with plasmids that have 342 been shown to facilitate the dissemination of successful resistance genes, even in the absence 343 of selection pressures, may represent a difficult situation to control (Stoesser et al, 2017).…”
mentioning
confidence: 99%
“…Isolates were re-cultured from frozen stocks stored in nutrient broth plus 10% Table 1) were de-novo assembled using Velvet 20 as previously described. 21 In silico Achtman 22 multi-locus sequence types (MLST) types were defined using ARIBA.…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…72 While antibiotic resistance is by definition necessary for a clone to become epidemic, it does not appear in itself sufficient, as there are numerous examples of less prominent clones having the same resistance determinants as their epidemic counterparts. 64,73,74 Far from being simply an academic exercise, understanding why certain lineages explode on the global scene is critical for more effective monitoring and early detection of emergent lineages of high epidemic potential. By applying evolutionary genomics approaches, investigators have begun to chart the evolutionary trajectories of epidemic lineages, which is an essential first step in understanding whether the success of these clones is due to chance accumulation of beneficial mutations or if the genetic background of these ancestral strains predisposed them to thrive in the antibiotic era.…”
Section: Evolution and Dissemination Of Clonal Lineagesmentioning
confidence: 99%